FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN DI KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Asrofiyah, Siti; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 6 (2023): Vol.12.6.JUNI.2023[376-450], 2023)
This study aims to analyze the factors influencing the income of fishermen in Muncar District, Banyuwangi Regency, and to examine the partial effects of capital, work experience, working hours, and technology on the income of fishermen in Muncar District, Banyuwangi Regency. The data used in this study are primary data. The population in this study is the number of fishermen in Muncar District. Purposive sampling combined with accidental sampling technique is used in this study. The total sample obtained is 82 fishermen, determined using the Slovin formula. The results of this study indicate that all variables have a positive and simultaneous influence on the income level in Muncar District. Capital, work experience, and technology have a positive and significant partial effect on the income of fishermen in Muncar District. However, working hours have a negative and nonsignificant partial effect on the income of fishermen in Muncar District, Banyuwangi Regency . keyword : Fishermen’s income, capital, work experience, working hours and technology